Effects of strength training on running economy - Guglielmo, L. G. A.; Greco, C. C.; Denadai, B. S. (International Journal of Sports Medicine, 2009)
The objective of this study was to compare the effect of different strength training protocols added to endurance training on running economy (RE). Sixteen well-trained runners (27.4 ± 4.4 years; 62.7 ± 4.3 kg; 166.1 ± 5.0 cm), were randomized into two groups: explosive strength training (EST) (n = 9) and heavy weight strength training (HWT) (n = 7) group. They performed the following tests before and after 4 weeks of training: 1) incremental treadmill test to exhaustion to determine of peak oxygen uptake and the velocity corresponding to 3.5 mM of blood lactate concentration; 2) submaximal constant-intensity test to determine RE; 3) maximal countermovement jump test and; 4) one repetition maximal strength test in leg press. After the training period, there was an improvement in RE only in the HWT group (HWT = 47.3 ± 6.8 vs. 44.3 ± 4.9 ml · kg-1 · min-1; EST = 46.4 ± 4.1 vs. 45.5 ± 4.1 ml · kg-1 · min-1). In conclusion, a short period of traditional strength training can improve RE in well-trained runners, but this improvement can be dependent on the strength training characteristics. When comparing to explosive training performed in the same equipment, heavy weight training seems to be more efficient for the improvement of RE.